Multispecies bioassay of propylparaben to derive protective concentrations for soil ecosystems using a species sensitivity distribution approach. (October 2020) - Kim, Dokyung; Kim, Lia; Kim, Dasom; Kim, Shin Woong; Kwak, Jin Il; Cui, Rongxue; An, Youn-Joo
Abstract: Propylparaben is widely used as a preservative in pharmaceuticals and personal care products and is ultimately excreted by the human body. Thus, propylparaben reaches sewage and enters the soil environment by sludge fertilization and wastewater irrigation. However, there are few existing studies on the toxicity and risks of such chemicals in terrestrial environments. In this study, a multispecies bioassay for propylparaben was performed and protective concentrations (PCs) were derived based on toxicity values by probabilistic ecological risk assessment. Acute and chronic bioassays were conducted on 11 species in eight taxonomic groups (Magnoliopsida, Liliopsida, Clitellata, Entognatha, Entomobryomorpha, Chromadorea, Chlorophyceae, Trebouxiophyceae). Based on the toxicity values calculated, the PC95 values for acute and chronic SSDs were 13 and 6 mg/kg dry soil, respectively. Toxicity varied among taxa, with soil algae emerging as the most sensitive to propylparaben. This may be attributable to differences in exposure pathways among species. The exposure pathway of propylparaben can be altered by adsorption to soil particles. As parabens are presently under-regulated globally in terms of their environmental effects, our findings can serve as the basis to propose standard values for environmental protection. Graphical abstract: Image 1 Highlights: The risk of propylparaben, an endocrine disruptor, to the soil ecosystem is unknown. Protective concentration was calculated based on species sensitivity distribution. Acute and chronic soil PC95 of propylparaben were 13 and 6 mg/kg, respectively. This study can serve to propose standard values for soil protection. Abstract : In this study, acute and chronic soil protective concentrations of propylparaben were estimated to protect soil ecosystems based on species sensitivity methods.